2017
DOI: 10.1016/j.jtcvs.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Open repair of chronic thoracic and thoracoabdominal aortic dissection using deep hypothermia and circulatory arrest

Abstract: Open repair of chronic thoracic and thoracoabdominal aortic dissection using deep hypothermia and circulatory arrest has low morbidity and mortality. The need for reintervention is low, and long-term survival is excellent. We believe that open repair continues to be the gold standard in patients who are suitable candidates for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…For operations involving the descending or thoracoabdominal aorta with or without arch replacement, our technique has been described elsewhere using deep hypothermia and circulatory arrest [27][28][29] Teflon-felt pledgets, which have high risk for reinfection, were avoided. Self-made CPA tissue pledgets were used if the anastomoses required hemostatic sutures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For operations involving the descending or thoracoabdominal aorta with or without arch replacement, our technique has been described elsewhere using deep hypothermia and circulatory arrest [27][28][29] Teflon-felt pledgets, which have high risk for reinfection, were avoided. Self-made CPA tissue pledgets were used if the anastomoses required hemostatic sutures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The authors have not suggested any significant difference resulting from a two staged approach in this large number of patients. In contrast, Corvera et al 3 suggested that open one stage repair of extended TAAA (69 patients with type II TAAA) using deep hypothermia and circulatory arrest has low morbidity, mortality, and re-intervention rates, while posing excellent long-term survival rates.…”
mentioning
confidence: 99%
“…Despite significant advances in the treatment of thoracoabdominal aortic aneurysm (TAA) and other acute aortic syndromes, the risk of ischemic spinal cord injury (SCI) is significant and remains a relatively common and devastating complication after both open surgery and endovascular surgery. 1,2 Years of research have enhanced our understanding of the complex pathophysiology surrounding this problem, including an evolved understanding of the importance of collateral circulation networks. 3 Although there was initial optimism that the transition from open surgery to endovascular approaches (ie, thoracic endovascular aortic repair) would see the end to SCI (or at least a significant reduction), this has not been the case.…”
mentioning
confidence: 99%